EU employment and social situation quarterly review - September 2014 (Luxembourg, 2014)
"Employment in the European Union (EU) has continued to grow at a steady pace and in most sectors. There has been an increase in the average number of hours worked and, for the first time since the third quarter of 2011, there was a small increase in the number of full-time contracts. Youth unemployment rates have decreased in most EU Member States and financial distress is continuing to ease, now also for the lowest income groups. In contrast, the gradual fall in unemployment rates observed since mid-2013 may have halted, as of June, and unemployment rates still remain close to historically high levels. Addressing long-term and very long-term unemployment is a major challenge in the context of the EU labour market recovery. The long-term unemployed make-up a significant share of total unemployment in the EU and – although stable at the EU level – the long-term unemployment rate is increasing in those Member States where it is already very high. It remains the case that much of the job creation is associated with the continuous increase in part-time and temporary contracts. The EU's tentative recovery appears to have lost some momentum and, therefore, future developments in employment remain uncertain. This highlights the importance of continued policy intervention to support the macro-economic and employment recovery in the EU and to improve the social situation of the population "